THE ASSOCIATION BETWEEN OBJECTIVELY MEASURED PHYSICAL ACTIVITY AND BONE STRENGTH AMONG OLDER MEN. (11th November 2018) - Langsetmo, L; Ensrud, K; Cauley, J; Cawthon, P; Burghardt, A
Abstract: To examine the association between objectively measured physical activity with bone strength of the distal limbs, we studied 994 older men (mean age 83.9 years, SD 3.9) from the MrOS study who had 5-day activity assessment with at least 90% wear time (SenseWear Pro3 Armband) at Y7 and Y14 Visit and who had a Y14 bone microarchitecture assessment (Scanco high resolution peripheral quantitative tomography [HR-pQCT]). Physical activity parameters were averaged over two time-points. Bone strength as measured by estimated failure load (force required to break) was determined from HR-pQCT bone scans using finite element analysis (higher values indicating greater strength). The mean (SD) daily energy expenditure was 2338 (356) kcal; the mean (SD) distal radius failure load was 4891 (1328) N; and the mean (SD) distal tibia failure load was 13, 634 (2942) N. The mean (SD) daily time spent in light (1.5–3 METs) activity was 67 (28) min and at least moderate (>3 METs) activity was 85 (52) min. Higher total energy expenditure was associated with higher (better) failure load of distal tibia (effect size=0.21 [95% CI: 0.14, 0.28]) and distal radius (effect size=0.13 [95% CI: 0.06–0.20]) after adjustment for age, race, weight, limb length, education, alcohol use, and smoking history. Time spent in at least moderate activity vs. time spent in sedentary behavior (<1.5 METs) was related to bone strength at both sites after adjustment, whereas time spent in light activity was not. These results suggest that physical activity may have a modest benefit on bone strength.